2012
DOI: 10.3844/ajassp.2012.1553.1560
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Severity and Environmental Health Risk Factor among Asthmatic Primary School Children in the Selected Areas

Abstract: Problem statement: The purpose of this study was to assess the severity of asthma and associated risk factors among asthmatic primary school children in the selected urban, industrial and rural areas of Selangor and Kuala Lumpur. Approach: A total of 207 respondents were involved in this study, in which 87 were children from the urban areas, 67 children were from the industrial areas and another 53 children were from rural areas. The selection of respondents was based on purposive sampling method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The study conducted by Zakaria et. al, [15] among a total of 207 school children in Klang Valley revealed that the presence of particulate matter can influence the severity of asthma among primary school children in urban, industrial, and rural areas of Selangor and Kuala Lumpur. Study by Pierse et al [16] reported a higher prevalence of cough without cold in a cohort of 4400 preschool children with increased exposure to locally generated particulate matter pollution mainly from the road.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study conducted by Zakaria et. al, [15] among a total of 207 school children in Klang Valley revealed that the presence of particulate matter can influence the severity of asthma among primary school children in urban, industrial, and rural areas of Selangor and Kuala Lumpur. Study by Pierse et al [16] reported a higher prevalence of cough without cold in a cohort of 4400 preschool children with increased exposure to locally generated particulate matter pollution mainly from the road.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term effects of PM 2.5 particles on children include both lung function changes and the development of chronic respiratory disease, while short-term exposures to PM 10 can result in increased respiratory symptoms. The concentrations of PM 10 were associated with wheezing among asthmatic school children in a study conducted by Zakaria et al [15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by a study from the World Health Organization (WHO) indicated approximately, 3.5 million people die early annually from indoor air pollution and 3.3 million from outdoor air pollution (Reuters, 2013). The effects of air pollution on respiratory symptoms (Gül et al, 2011;Liu et al, 2013;Tabaku et al, 2011), asthma attacks (Zakaria et al, 2012) and lung function (Linares et al, 2010) have been shown.…”
Section: Introductionmentioning
confidence: 99%